KEPASTIAN HUKUM JAMINAN HAK TANGGUNGAN ATAS SERTIFIKAT HAK PAKAI DI ATAS HAK MILIK PERORANGAN TERKAIT PENOLAKAN PEMBIAYAAN OLEH PERBANKAN. - Aziz, Abdul; Franciska, Wira; Marniati, Felicitas Sri (LPPM Institut Pendidikan Nusantara Global, 2023)
Seeing the increasing focus on the economic sector, it requires a guarantee rights institution that is able to provide legal certainty. In the UUHT, land rights can be made into mortgages, property rights, business use rights, building use rights and use rights over state land, while PP 18 of 2021 explains usufructuary rights can be used as collateral for mortgage rights. In the phenomenon that occurs, usufructuary rights over individual rights experience rejection by the banking system when they are used as collateral for mortgage rights. Based on these problems, the formulation of the problem is how to implement guarantees for usufructuary certificates over individual property rights related to refusal of financing by banks and how legal certainty guarantees mortgage rights over usufructuary certificates over individual property rights related to refusal of financing by banks. The theory used is Legal Certainty from Gustav Radbruch and Satrio's Guarantee Law Theory. The method used in this study is normative juridical research, namely library law research or secondary data with sources of primary, secondary and tertiary legal materials, supported by interviews. The research approach used is the statutory approach, conceptual approach, analytical approach and case approach, and legal material collection techniques are carried out by identifying and inventorying positive legal rules, literature books, journals and other sources of legal materials. For technical analysis of legal material, it is carried out by means of legal interpretation (interpretation) of grammatical interpretation and systematic interpretation and methods of legal construction. The results of research on usufructuary rights on individual land cannot be encumbered with mortgage rights, this makes it ambiguous between the UUHT and PP 18 of 2021. There needs to be an affirmation in PP 18 of 2021 as well as the guarantee of usufructuary rights so that they can be in line with UUHT